Perbedaan Sonopattern Ultrasonografi Kandung Empedu pada Kasus Cholelithiasis & Galbladder Polyp - Fiddinillah Fiddinillah; Sriyatun Sriyatun; Nurbaiti Nurbaiti; Nursama Heru Apriantoro (FORUM ILMIAH KESEHATAN, 2021)
On ultrasound examination of the gallbladder Cholelithiasis and Gallbladder Polyp usually have similar results but have their own characteristics that can differentiate. In the image results Cholelithiasis, which is usually called gallstones, has a characteristic Sonopattern Hyperechoic with an Acousstic Shadow behind it, where when using the technique the patient's position changes the stone according to the direction of Earth's gravity. While the results of the Gallbladder Polyp image, which is a tumor protrusion attached to the gallbladder wall, has the characteristic Sonopattern Hyperecoic without an acoustic shadow behind it, where when using the technique the patient's position changes not according to the direction of Earth's gravity. In both cases, the presence or absence of an acoustic shadow behind it is based on the density of the tissue that the sound waves pass through from the ultrasound device, so that when passing through the stone, the acoustic shadow is more visible than when passing through the tumor tissue.. Keywords: sonopattern ultrasound; cholelithiasis; gallbladder polyp ABSTRAK Pada pemeriksaan USG kandung empedu Cholelithiasis dan Gallbladder Polyp biasanya memiliki hasil gambaran yang serupa tetapi memiliki ciri khasnya masing-masing yang dapat membedakan. Pada hasil gambaran Cholelithiasis yang biasa disebut batu empedu memiliki ciri khas Sonopattern Hyperechoic dengan Acousstic Shadow di belakangnya, ketika menggunakan teknik dengan posisi pasien yang berubah batu mengikuti arah gravitasi bumi. Sementara pada hasil gambaran Gallbladder Polyp yang merupakan tonjolan tumor yang menempel pada dinding kandung empedu memiliki ciri khas Sonopattern Hyperecoic tanpa Accoustic Shadow dibelakangnya, dimana ketika menggunakan teknik dengan posisi pasien yang berubah tidak mengikuti arah gravitasi bumi. Pada kedua kasus ini ada tidaknya Accoustic Shadow di belakangnya didasari oleh kepadatan jaringan yang dilalui oleh gelombang suara dari alat USG, sehingga saat melewati batu lebih tampak Accoustic Shadow dibandingkan saat melewati jaringan tumor. Kata kunci: sonopattern ultrasound; cholelithiasis; gallbladder polyp